Konsekwencje prawne opatrzenia danych podpisem osobistym w stosunku do innego podmiotu niż podmiot publiczny - Bierecki, Dominik (PRAWO i WIĘŹ, 2024)
Accordingly to Polish regulation on ID card, the electronic layer of the ID card contains a personal signature certificate along with the signature data. The personal signature is an advanced electronic signature under eIDAS. Due to parties agreement the personal signature can become an equivalent of the handwritten signature. This results in fulfilling the requirement of a written form of a legal action reserved ad soleminitatem, ad probationem or ad eventum.